RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB UNTUK EFEKTIVITAS LAYANAN PEMINJAMAN DAN PENGEMBALIAN BUKU - Farah Hanin Dhiya Amanda (Teknik Informatika Fakultas Ilmu Komputer, 2022)
The library is one of the facilities that support the learning activities of students or students to get references or sources of knowledge and information. With the development of technology, people think to be able to work more effectively and efficiently. One of them is to make the conventional system into a computerized system. By utilizing the facilities of a website that is connected to the internet, the library can be more and more efficient. The purpose of this study is to design a web-based library information system to help librarians solve problems in school libraries. In this study, a web-based information system was designed using the PHP MySQL programming language. With this system, it is hoped that it will be able to overcome various needs to find books and facilitate school administration in borrowing books and making reports.